Pengaruh Desain Rak Sepatu Terhadap Tingkat Kelembaban Didalamnya - Friska Damayanti; Prasiska Damastuti; Eilsa Adelia (JIE Scientific Journal on Research and Application of Industrial System, 2023)
The existence of shoe racks has become one of the needs in every residential house and certain building facilities. So far, the design of shoe racks is often neglected both in terms of design and also moisture considerations. Shoes stored in a storage area are susceptible to fungal growth triggered by high humidity in them and can shorten the life of shoes. This study aims to find out the influence of shoe rack design in this case is the ventilation applied to the shelf door design against the moisture inside, so that the shoe rack can function optimally. Humidity measurements were made on 3 shoe racks with 3 door hole design modifications. Modification 1 is a door without ventilation holes, modification 2 is a door with ventilation on part of the door and modification 3 is a door with ventilation on the entire door. Based on the results of humidity measurements on the three modifications, it was obtained that the larger the ventilation holes on the rack, the lower the humidity in it.